System dynamics modelling of India’s net zero transition - Ramya Natarajan; Aparna Sundaresan; Kaveri Ashok; Anasuya Gangopadhyay; Divya Davis; Krithika Ravishankar; Sweta Bhushan; Sarah Khan; Kunal Jagdale; Upasna Ranjan; Chandrakiran L; Indu K Murthy; et al. (Energy and Climate Change, 2026)

Trigonelline, a natural alkaloid, mitigates nanoplastic-induced neurotoxicity by restoring mitochondrial function and redox homeostasis in Drosophila melanogaster - Priya Rathor; Ashutosh K. Tiwari; Adarsh Kumar; Anurag Mathur; Abha Meena; Sheetal Rana; Ratnasekhar CH (Food and Chemical Toxicology, 2026)

Integrated cytotoxicity screening and in silico analysis of coumarin nucleoside conjugates as computationally modeled VEGFR-2 inhibitors: oncocyte cytotoxicity, molecular docking, and dynamics simulation studies - Divya Mathur; Vipin K. Maikhuri; Sushma Yadav; Nidhi Bhardwaj; Shreya Pandey; Hangshika Sharma; Meenakshi Thakur; Alok Chandra Bharti; Debdip Bhandary; Anna Senrung (In Silico Pharmacology, 2025)

Stronger Together: The Role of the Community Dietitian in Supporting Families Affected by Alzheimer’s and Other Dementias - L. Hughes; S. Mathur; M. Kane; K. Cullinen (Journal of the Academy of Nutrition and Dietetics, 2025)

Decoding of physiological and molecular mechanisms for breeding of drought tolerant crops - Ratnakumar Pasala; Brij Bihari Pandey; ChLN Manikanta; Arun K. Shanker; K. Ramesh; Subramaniam Geethanjali; Amaranatha R. Vennapusa; Kalpalatha Melmaiee; Pooja Srivastava; Amber Gupta; Yogeshwar Singh; Sanket J. More; et al. (Plant Physiology Reports, 2025)

Development of a Power Operated Fenugreek Thresher - C. Naveen Kumar; R. K. Rathod; T. Nageshkumar; S. M. Mathur (Agricultural Research, 2025)

Integrated geospatial and statistical analysis of urban air pollutants (PM10, SO2 and NO2) and their relationships with land surface temperature over a semi-arid environment - Monika Sharma; Porush Kumar; Mahendra Pratap Choudhary; Anil K. Mathur (Environmental Monitoring and Assessment, 2025)

Hesperetin-supplemented soybean and ginger hydroalcoholic extracts alleviate diabetic cardiomyopathy in streptozotocin induced diabetic rats by modulating NF-κB/MMP-9/TIMPs pathway - Ritu; Ravinder Verma; Sudhir Kaushik; Prabhnain Kaur; Pooja Mathur; T. Velpandian; Ramesh K Goyal (South African Journal of Botany, 2025)

In-silico prediction of coat protein structure of Indian citrus ringspot virus and their interactions with the Argonaut2/DCL4 proteins - Aniket Angira; Siddharth Yadav; Puniti Mathur; V. K. Baranwal; Aashish Ranjan; Nandlal Choudhary (VirusDisease, 2025)

Treatment of textile effluent by electrocoagulation in a novel reactor to mitigate environmental pollution - P. Agarwal; V. K. Sangal; S. Mathur (International Journal of Environmental Science and Technology, 2025)

BRCAIndica: a resource for ACMG/AMP classified BRCA1 and BRCA2 variants - Aastha Vatsyayan; R. I. Anu; Prerika Mathur; Divya Uchil; Ashish Joshi; Aradhana Dwivedi; Bhawna Sirohi; Aju Mathew; Dileep Damodaran; Soumya Surath Panda; Spoorthy Kolluri; Shaji K. Ayillath; et al. (Familial Cancer, 2025)

Correlation Between Space Borne Night-Time Light Data and Seismic Activity in Mountainous Region of Shughnon, Tajikistan - Mathur Mudit; Sanjay Bhatia; Praveen K Thakur; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2025)

Exploring spatial dynamics of urbanization and solid waste generation in Kota city using the Google Earth Engine - Porush Kumar; Mahendra Pratap Choudhary; Anil K. Mathur (Environmental Monitoring and Assessment, 2025)

Public views about the world's largest proposed solar farm in remote Australia - Kerstin K. Zander; Deepika Mathur; Supriya Mathew; Stephen T. Garnett (Energy Policy, 2024)

Cytokinin oxidase2-deficient mutants improve panicle and grain architecture through cytokinin accumulation and enhance drought tolerance in indica rice - Afreen Rashid; V. Mohan M. Achary; M. Z. Abdin; Sangeetha Karippadakam; Hemangini Parmar; Varakumar Panditi; Ganesan Prakash; Pooja Bhatnagar-Mathur; Malireddy K. Reddy (Plant Cell Reports, 2024)

Deciphering the effect of Chlorella minutissima incorporation in gluten-free millet cookies: Physical and functional properties - Koushalya Selvaraju; Megha Mathur; Satheeshkanth SSM; Jatindra K. Sahu; P. Hariprasad; Anushree Malik (Algal Research, 2024)

Exploring component traits of biomass and yield in Indian rice mini-core germplasm - Chandrapal Vishwakarma; Sourabh Karwa; Riti Thapar Kapoor; Komal Mathur; G. K. Krishna; Rakesh Pandey; Ranjith K. Ellur; Gopalakrishnan Subbaiyan; K. K. Vinod; Viswanathan Chinnusamy (Plant Physiology Reports, 2024)

Immobilization of microbial multienzyme preparation on calcium alginate beads as well as lyophilization with mosambi peel matrix improved its shelf-life and stability - Balvindra Singh; Sumit K. Soni; Supriya Vaish; Priti Mathur; Neelima Garg (Folia Microbiologica, 2024)

Assessment and Threat to Significant Geoheritage of Soorsagar Formation of Jodhpur Group of Marwar Supergroup, Western Rajasthan, India: A Geological and Remote Sensing Approach - Saurabh Mathur; Sudhanshu Sharma; S. K. Singh; M. G. Thakkar; Gaurav Chauhan; Shiv Singh Rathore; S. C. Mathur (Geoheritage, 2023)

Chickpea Defensin Gene Family: Promising Candidates for Resistance Against Soil-Borne Chickpea Fungal Pathogens - Rahul B. Nitnavare; Arunima Pothana; Richa K. Yeshvekar; Joorie Bhattacharya; Vidhi Sapara; Palakolanu Sudhakar Reddy; Yogendra Ramtirtha; Avijit Tarafdar; Mamta Sharma; Pooja Bhatnagar-Mathur (Journal of Plant Growth Regulation, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

Precise utilization of fruit and vegetable waste as a substrate for the multienzyme production by Bacillus subtilis NG105 and Trichoderma asperelllum NG125 - Balvindra Singh; Sumit K. Soni; Neelima Garg; Priti Mathur (Biocatalysis and Agricultural Biotechnology, 2023)

Plastome characterization of Musa indandamanensis, an endemic banana in Andaman and Nicobar Islands, India - Satish Maurya; Vitthal T. Barvkar; Ritesh K. Choudhary; Lalji Singh; Mayank D. Dwivedi; Mudavath C. Naik; Gautam A. Ekka; Manish Kandwal; Roshni R. Mathur; Arun K. Pandey (The Nucleus, 2023)

A novel QTL linked to asparagine synthetase gene for stem height increment in oil palm (E. guineensis Jacq.) identified and validated through integrated genomic approaches - B. Kalyana Babu; R. K. Mathur; G. Ravichandran; P. Anitha; H. P. Bhagya; M. V. B. Venu (Euphytica, 2023)

Late Cretaceous–Early Paleocene Geodiversity of Fatehgarh Formation of Petroliferous Barmer Basin, Western Rajasthan, India: A Potential Geopark Site - Saurabh Mathur; Sudhanshu Sharma; S. K. Singh; S. S. Rathore; S. C. Mathur (Geoheritage, 2023)

Investigation of metasomatism using Cu, Zn and Fe stable isotopes: Rodingitization of mafic and ultramafic rocks in ophiolites from northern Greece - N. Zaronikola; V. Debaille; A. Rogkala; P. Petrounias; R. Mathur; S. Decrée; P. Pomonis; K. Hatzipanagiotou; B. Tsikouras (Lithos, 2023)

Species Composition and Diversity Dynamics of Actinomycetes in Arid and Semi-arid Salt Basins of Rajasthan - Khushbu Parihar; Praveen Gehlot; Manish Mathur; Alkesh Tak; Rakesh Pathak; Sunil K. Singh (Current Microbiology, 2022)

Microbial production of multienzyme preparation from mosambi peel using Trichoderma asperellum - Balvindra Singh; Neelima Garg; Priti Mathur; Sumit K. Soni; Supriya Vaish; Sanjay Kumar (Archives of Microbiology, 2022)

Assessment and Spatial Distribution Mapping of Criteria Pollutants - Kuldeep Kamboj; Sohil Sisodiya; Anil K. Mathur; Ali Zare; Puneet Verma (Water, Air, & Soil Pollution, 2022)
This study aims to assess the urban air quality, and map NO 2 , SO 2 , and PM 10 profiles using two widely spatial interpolation methods, ordinary kriging (OK) and inverse distance weighting (IDW) by estimating their concentrations at distinct non-monitored locations. Assessment and mapping of air pollutants in this study help with policy formulation and decision-making. Kota, the industrial and educational hub of Rajasthan (India), has been selected to study air quality. Results showed that PM 10 is continuously emerging as a foremost contributor to air quality index (AQI) each season. The concentrations of NO 2 and SO 2 in all seasons were well below the permissible level prescribed by the Central Pollution Control Board (CPCB). Interpolation techniques (OK and IDW) estimated the concentrations of NO 2 , SO 2 , and PM 10 at three sites using air quality data from the year 2019. The interpolated air pollutant results for the specified region were compared with monitored air quality data in the same region. An excellent agreement has been observed by comparing monitored values, and the values predicted from IDW and OK.

Chikungunya virus non-structural protein nsP3 interacts with Aedes aegypti DEAD-box helicase RM62F - Ramesh Kumar; Priyanshu Srivastava; Kalika Mathur; Jatin Shrinet; Sunil Kumar Dubey; Mahendran Chinnappan; Inderjeet Kaur; Debasis Nayak; Soma Chattopadhyay; Raj K. Bhatnagar; Sujatha Sunil (VirusDisease, 2021)

Correction to: Qualitative Assessment of Geoheritage for Geotourism Promotion: a Case Study from Mehrangarh Ridge in Jodhpur City, Western Rajasthan, India - Mathur Saurabh; Sharma Sudhanshu; Singh S. K.; Mathur S. C. (Geoheritage, 2021)

A Photorhabdus akhurstii toxin altered gut homeostasis prior conferring cytotoxicity in Spodoptera frugiperda, S. litura and Helicoverpa armigera - Tushar K. Dutta; Kodhandaraman Santhoshkumar; Chetna Mathur; Abhishek Mandal; Doddachowdappa Sagar (Phytoparasitica, 2021)

Qualitative Assessment of Geoheritage for Geotourism Promotion: a Case Study from Mehrangarh Ridge in Jodhpur City, Western Rajasthan, India - Mathur Saurabh; Sharma Sudhanshu; Singh S. K.; Mathur S. C. (Geoheritage, 2021)

Biodegradable and Biocompatible 3D Constructs for Dental Applications: Manufacturing Options and Perspectives - Deepika Sharma; Vijay Prakash Mathur; Bhabani K. Satapathy (Annals of Biomedical Engineering, 2021)

Phenomics, genomics of oil palm (Elaeis guineensis Jacq.): way forward for making sustainable and high yielding quality oil palm - B. Kalyana Babu; R. K. Mathur; P. Anitha; G. Ravichandran; H. P. Bhagya (Physiology and Molecular Biology of Plants, 2021)

An update and perspectives on the use of promoters in plant genetic engineering - Divya Kummari; Sudhakar Reddy Palakolanu; P B Kavi Kishor; Pooja Bhatnagar-Mathur; Prasanth Singam; Vincent Vadez; Kiran K Sharma (Journal of Biosciences, 2020)

Identification of QTLs in oil palm (Elaeis guineensis Jacq.) using SSR markers through association mapping - H. P. Bhagya; B. Kalyana Babu; P. M. Gangadharappa; Mahantesha B. N. Naika; D. Satish; R. K. Mathur (Journal of Genetics, 2020)

Tricuspid Valve Annuloplasty Alters Leaflet Mechanics - Mrudang Mathur; William D. Meador; Tomasz Jazwiec; Marcin Malinowski; Tomasz A. Timek; Manuel K. Rausch (Annals of Biomedical Engineering, 2020)

Comparing transformation pathways across major economies - R. Schaeffer; A. Köberle; H. L. van Soest; C. Bertram; G. Luderer; K. Riahi; V. Krey; D. P. van Vuuren; E. Kriegler; S. Fujimori; W. Chen; C. He; et al. (Climatic Change, 2020)

A Study on Impact of BPA in the Adipose Tissue Dysfunction (Adiposopathy) in Asian Indian Type 2 Diabetes Mellitus Subjects - Jyoti Jain; Nidhi Gupta; Rati Mathur; Surendra Nimesh; Sandeep K. Mathur (Indian Journal of Clinical Biochemistry, 2020)

Multifaceted genome-wide study identifies novel regulatory loci in SLC22A11 and ZNF45 for body mass index in Indians - Anil K. Giri; Gauri Prasad; Khushdeep Bandesh; Vaisak Parekatt; Anubha Mahajan; Priyanka Banerjee; Yasmeen Kauser; Shraddha Chakraborty; Donaka Rajashekar; Abhay Sharma; Sandeep Kumar Mathur; Analabha Basu; et al. (Molecular Genetics and Genomics, 2020)

Development of pepper vein banding virus chimeric virus-like particles for potential diagnostic and therapeutic applications - Pallavi Sabharwal; C. Sushmitha; C. K. Amritha; Usha Natraj; Mathur R. N. Murthy; Handanahal S. Savithri (Archives of Virology, 2020)

The Effect of Downsizing on the Normal Tricuspid Annulus - Mrudang Mathur; William D. Meador; Tomasz Jazwiec; Marcin Malinowski; Tomasz A. Timek; Manuel K. Rausch (Annals of Biomedical Engineering, 2020)

Isolation and functional characterization of three abiotic stress-inducible (Apx, Dhn and Hsc70) promoters from pearl millet (Pennisetum glaucum L.) - Kummari Divya; P. B. Kavi Kishor; Pooja Bhatnagar-Mathur; Prashanth Singam; Kiran K. Sharma; Vincent Vadez; Palakolanu Sudhakar Reddy (Molecular Biology Reports, 2019)

Genome-wide association study (GWAS) for stem height increment in oil palm (Elaeis guineensis) germplasm using SNP markers - B. Kalyana Babu; R. K. Mathur; G. Ravichandran; M. V. B. Venu (Tree Genetics & Genomes, 2019)

Salicylic acid and ultrasonic stress modulated gene expression and ginsenoside production in differentially affected Panax quinquefolius (L.) and Panax sikkimensis (Ban.) cell suspensions - Tanya Biswas; Archana Mathur; Vikrant Gupta; Manju Singh; A. K. Mathur (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Calcium ionophore enhanced developmental competence and apoptotic dynamics of goat parthenogenetic embryos produced in vitro - Diksha Dua; D. Nagoorvali; M.S. Chauhan; P. Palta; P. Mathur; M. K. Singh (In Vitro Cellular & Developmental Biology - Animal, 2019)

Enhanced expression of ginsenoside biosynthetic genes and in vitro ginsenoside production in elicited Panax sikkimensis (Ban) cell suspensions - Tanya Biswas; Shiv Shanker Pandey; Deepamala Maji; Vikrant Gupta; Alok Kalra; Manju Singh; Archana Mathur; A. K. Mathur (Protoplasma, 2018)

Day-1 INSAT-3DR Vicarious Calibration Using Reflectance-Based Approach Over Great Rann of Kutch - Piyushkumar N. Patel; K. N. Babu; R. P. Prajapati; Vikram Sitapara; A. K. Mathur (Journal of the Indian Society of Remote Sensing, 2018)

Copper-Induced Modulation of Biomass Growth, Physiological Parameters, Bioactive Centellosides, and Expression of Biosynthetic Pathway Genes in an Important Medicinal Herb, Centella asiatica - Archana Prasad; Mamta Kumari; N. K. Srivastava; A. K. Mathur; Archana Mathur (Journal of Plant Growth Regulation, 2018)

Indian spinach: an underutilized perennial leafy vegetable for nutritional security in developing world - Ajeet Singh; Pradeep K. Dubey; Rajan Chaurasiya; Nitin Mathur; Gangesh Kumar; Sujeet Bharati; P. C. Abhilash (Energy, Ecology and Environment, 2018)

A novel mitochondrial orf147 causes cytoplasmic male sterility in pigeonpea by modulating aberrant anther dehiscence - Pooja Bhatnagar-Mathur; Ranadheer Gupta; Palakolanu Sudhakar Reddy; Bommineni Pradeep Reddy; Dumbala Srinivas Reddy; C. V. Sameerkumar; Rachit Kumar Saxena; Kiran K. Sharma (Plant Molecular Biology, 2018)

Feasibility study of waste (d) potential: co-digestion of organic wastes, synergistic effect and kinetics of biogas production - K. Paritosh; S. Mathur; N. Pareek; V. Vivekanand (International Journal of Environmental Science and Technology, 2018)

Erratum to: Linear Analysis of Autonomic Activity and Its Correlation with Creatine Kinase-MB in Overt Thyroid Dysfunctions - Manisha Mavai; Yogendra Raj Singh; R. C. Gupta; Sandeep K. Mathur; Bharti Bhandari (Indian Journal of Clinical Biochemistry, 2018)

Linear Analysis of Autonomic Activity and Its Correlation with Creatine Kinase-MB in Overt Thyroid Dysfunctions - Manisha Mavai; Yogendra Raj Singh; R. C. Gupta; Sandeep K. Mathur; Bharti Bhandari (Indian Journal of Clinical Biochemistry, 2018)

INSAT-3D and MODIS retrieved sea surface temperature validation and assessment over waters surrounding the Indian subcontinent - Geetika Tyagi; K. N. Babu; A. K. Mathur; H. A. Solanki (International Journal of Remote Sensing, 2018)

Radiometric calibration stability assessment for the RISAT-1 SAR sensor using a deployed point target array at the Desalpar site, Rann of Kutch, India - Shweta Sharma; Gautam Dadhich; Mihir Rambhia; Aloke K. Mathur; R.P Prajapati; P.R Patel; Alpana Shukla (International Journal of Remote Sensing, 2017)

Economic efficiency and its effect on cost: a case study of organic pineapple in India’s northeast - Ujjwal K. Paul; Gurudas Das; Tanuj Mathur; Avijit Debnath (Organic Agriculture, 2017)

Enhancing forage production through a silvi-pastoral system in an arid environment - M. Patidar; B. K. Mathur (Agroforestry Systems, 2017)

Potential of Crop Residue and Fertilizer on Enrichment of Carbon Pools in Upland Soils of Subtropical India - P. K. Ghosh; K. K. Hazra; M. S. Venkatesh; K. K. Singh; Narendra Kumar; R. S. Mathur (Agricultural Research, 2016)

Layout and Component Size Optimization of Sewer Network Using Spanning Tree and Modified PSO Algorithm - Praveen K. Navin; Yogesh P. Mathur (Water Resources Management, 2016)

Genistein ameliorates cardiac inflammation and oxidative stress in streptozotocin-induced diabetic cardiomyopathy in rats - Suresh K. Gupta; Shirish Dongare; Rajani Mathur; Ipseeta Ray Mohanty; Sushma Srivastava; Sandeep Mathur; Tapas C. Nag (Molecular and Cellular Biochemistry, 2015)

Erratum to: Unique miRNome during anthesis in drought-tolerant indica rice var. Nagina 22 - Shivani Kansal; Roseeta Devi Mutum; Sonia C. Balyan; Mukesh K. Arora; Ashok Kumar Singh; Saloni Mathur; Saurabh Raghuvanshi (Planta, 2015)

Unique miRNome during anthesis in drought-tolerant indica rice var. Nagina 22 - Shivani Kansal; Roseeta M. Devi; Sonia C. Balyan; Mukesh K. Arora; Anil K. Singh; Saloni Mathur; Saurabh Raghuvanshi (Planta, 2015)

DREB1A overexpression in transgenic chickpea alters key traits influencing plant water budget across water regimes - Krithika Anbazhagan; Pooja Bhatnagar-Mathur; Vincent Vadez; Srinivas Reddy Dumbala; P. B. Kavi Kishor; Kiran K. Sharma (Plant Cell Reports, 2015)

Over-expression of Catharanthus roseus tryptophan decarboxylase and strictosidine synthase in rol gene integrated transgenic cell suspensions of Vinca minor - Priyanka Verma; Abhishek Sharma; Shamshad Ahmad Khan; Karuna Shanker; Ajay K. Mathur (Protoplasma, 2015)

Rapid, accurate and routine HPLC method for large-scale screening of pro-vitamin A carotenoids in oilseeds - Madhurima Bhatnagar-Panwar; Pooja Bhatnagar-Mathur; Venkata VijayAnand Bhaaskarla; Srinivas Reddy Dumbala; Kiran K. Sharma (Journal of Plant Biochemistry and Biotechnology, 2015)

A multi-step phosphorelay two-component system impacts on tolerance against dehydration stress in common wheat - Vijay Gahlaut; Saloni Mathur; Raman Dhariwal; Jitendra P. Khurana; Akhilesh K. Tyagi; Harindra S. Balyan; Pushpendra K. Gupta (Functional & Integrative Genomics, 2014)

Improved sanguinarine production via biotic and abiotic elicitations and precursor feeding in cell suspensions of latex-less variety of Papaver somniferum with their gene expression studies and upscaling in bioreactor - Priyanka Verma; Shamshad Ahmad Khan; Ajay K. Mathur; Sumit Ghosh; Karuna Shanker; Alok Kalra (Protoplasma, 2014)

28-Homobrassinolide: a novel oxysterol transactivating LXR gene expression - R. Premalatha; K. Srikumar; D. Vijayalaksmi; G. N. Kumar; P. P. Mathur (Molecular Biology Reports, 2014)

Fungal endophytes enhanced the growth and production kinetics of Vinca minor hairy roots and cell suspensions grown in bioreactor - Priyanka Verma; Shamshad Ahmad Khan; Ajay K. Mathur; Karuna Shanker; Alok Kalra (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

In vitro propagation and biosynthesis of steroidal sapogenins from various morphogenetic stages of Moringa oleifera Lam., and their antioxidant potential - Manas Mathur; Sunita Yadav; Pawan K. Katariya; Raka Kamal (Acta Physiologiae Plantarum, 2014)

Enhanced Interaction of Shuffled Mutacin IV, an Antimicrobial Peptide of Bacterial Origin, with Surface Protein IsdB of Staphylococcus aureus - Chakresh K. Jain; Raman Sethi; Vanashika Sharma; Ashwani Mathur; Sanjeev K. Sharma (International Journal of Peptide Research and Therapeutics, 2014)

Remediation of LNAPL Contaminated Groundwater Using Plant-Assisted Biostimulation and Bioaugmentation Methods - Brijesh K Yadav; Faiz A Ansari; Shreejita Basu; Anuj Mathur (Water, Air, & Soil Pollution, 2014)

Channel Characteristics and Planform Dynamics in the Indian Terai, Sharda River - Neha Midha; Pradeep K. Mathur (Environmental Management, 2014)

Semen quality of environmentally exposed human population: the toxicological consequence - Niraj Pant; A. B. Pant; P. K. Chaturvedi; M. Shukla; N. Mathur; Y. K Gupta; D. K. Saxena (Environmental Science and Pollution Research, 2013)

Overexpression of a chitinase gene in transgenic peanut confers enhanced resistance to major soil borne and foliar fungal pathogens - Kalyani Prasad; Pooja Bhatnagar-Mathur; Farid Waliyar; Kiran K. Sharma (Journal of Plant Biochemistry and Biotechnology, 2013)

Tryptophan over-producing cell suspensions of Catharanthus roseus (L) G. Don and their up-scaling in stirred tank bioreactor: detection of a phenolic compound with antioxidant potential - Priyanka Verma; Ajay K. Mathur; Nusrat Masood; Suaib Luqman; Karuna Shanker (Protoplasma, 2013)

Particulate matter concentration in ambient air and its effects on lung functions among residents in the National Capital Region, India - C. Kesavachandran; B. S. Pangtey; V. Bihari; M. Fareed; M. K. Pathak; A. K. Srivastava; N. Mathur (Environmental Monitoring and Assessment, 2013)

Pathogen-derived resistance using a viral nucleocapsid gene confers only partial non-durable protection in peanut against peanut bud necrosis virus - S. Chander Rao; P. Bhatnagar-Mathur; P. Lava Kumar; A. Sudarshan Reddy; Kiran K. Sharma (Archives of Virology, 2013)

Enhanced vincamine production in selected tryptophan-overproducing shoots of Vinca minor - Priyanka Verma; Ajay K. Mathur; Karuna Shanker (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Growth and asiaticoside production in multiple shoot cultures of a medicinal herb, Centella asiatica (L.) Urban, under the influence of nutrient manipulations - Archana Prasad; Archana Mathur; Manju Singh; Madan M. Gupta; Girish C. Uniyal; Raj K. Lal; Ajay K. Mathur (Journal of Natural Medicines, 2012)

Japanese Encephalitis: A Persistent Threat - Aditi Singh; Shailendra K. Saxena; Apurva K. Srivastava; Asha Mathur (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2012)

Growth, alkaloid production, rol genes integration, bioreactor up-scaling and plant regeneration studies in hairy root lines of Catharanthus roseus - P Verma; A K. Mathur; K Shanker (Plant Biosystems, 2012)

Glycyrrhiza glabra (Linn.) and Lavandula officinalis (L.) cell suspension cultures-based biotransformation of β-artemether - Suman Patel; Rashmi Gaur; Mohita Upadhyaya; Archana Mathur; Ajay K. Mathur; Rajendra S. Bhakuni (Journal of Natural Medicines, 2011)

Bioremediation of Pulp and Paper Mill Effluent by Tannic Acid Degrading Enterobacter sp. - Yogendra Prakash Singh; Purnima Dhall; R. M. Mathur; R. K. Jain; Vasanta vadde Thakur; Virendra Kumar; Rita Kumar; Anil Kumar (Water, Air, & Soil Pollution, 2011)

Atmospheric correction for sea surface temperature retrieval from single thermal channel radiometer data onboard Kalpana satellite - NAVEEN R SHAHI; NEERAJ AGARWAL; ALOKE K MATHUR; ABHIJIT SARKAR (Journal of Earth System Science, 2011)

An assessment of the potential impact of climate change on flood risk in Mumbai - Nicola Ranger; Stéphane Hallegatte; Sumana Bhattacharya; Murthy Bachu; Satya Priya; K. Dhore; Farhat Rafique; P. Mathur; Nicolas Naville; Fanny Henriet; Celine Herweijer; Sanjib Pohit; et al. (Climatic Change, 2011)

Mammal indicator species for protected areas and managed forests in a landscape conservation area of northern India - Pradeep K. Mathur; Harish Kumar; John F. Lehmkuhl; Anshuman Tripathi; Vishwas B. Sawarkar; Rupak De (Biodiversity and Conservation, 2011)

Identification of quantitative trait loci associated with resistance to foliar diseases in sorghum [Sorghum bicolor (L.) Moench] - S. Murali Mohan; R. Madhusudhana; K. Mathur; D. V. N. Chakravarthi; Sanjay Rathore; R. Nagaraja Reddy; K. Satish; G. Srinivas; N. Sarada Mani; N. Seetharama (Euphytica, 2010)

Occurrence of phthalic acid esters in Gomti River Sediment, India - Abhinav Srivastava; Vinod P. Sharma; Ranu Tripathi; Rakesh Kumar; Devendra K. Patel; Pradeep Kumar Mathur (Environmental Monitoring and Assessment, 2010)

Assessment of forest fragmentation in the conservation priority Dudhwa landscape, India using FRAGSTATS computed class level metrics - N. Midha; P. K. Mathur (Journal of the Indian Society of Remote Sensing, 2010)

Influence of cellular differentiation and elicitation on intermediate and late steps of terpenoid indole alkaloid biosynthesis in Catharanthus roseus - Ashutosh K. Shukla; Ajit K. Shasany; Ram K. Verma; Madan M. Gupta; Ajay K. Mathur; Suman P. S. Khanuja (Protoplasma, 2010)

An efficient method for the production of marker-free transgenic plants of peanut (Arachis hypogaea L.) - Madhurima Bhatnagar; Kalyani Prasad; Pooja Bhatnagar-Mathur; M. Lakshmi Narasu; Farid Waliyar; Kiran K. Sharma (Plant Cell Reports, 2010)

Development of isopluvial map using L-moment approach for Tehri-Garhwal Himalaya - S. Sarkar; N. K. Goel; B. S. Mathur (Stochastic Environmental Research and Risk Assessment, 2010)

Growth kinetics and ginsenosides production in transformed hairy roots of American ginseng—Panax quinquefolium L - Archana Mathur; Anita Gangwar; Ajay K. Mathur; Priyanka Verma; Girish C. Uniyal; Raj K. Lal (Biotechnology Letters, 2010)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Elucidating the site of action of oxalate in photosynthetic electron transport chain in spinach thylakoid membranes - Anjana Jajoo; Archna Sahay; Pooja Singh; Sonal Mathur; Sergei K. Zharmukhamedov; Vyacheslav V. Klimov; Suleyman I. Allakhverdiev; Sudhakar Bharti (Photosynthesis Research, 2008)

Distribution analysis of salt affected soils under canal and non-canal command area in a part of Etah district, U. P., using remote sensing technique - A. K. Singh; P. K. Singh; B. Lal; A. N. Singh; A. Mathur (Journal of the Indian Society of Remote Sensing, 2008)

Improved guggulsterone production from sugars, precursors, and morphactin in cell cultures of Commiphora wightii grown in shake flasks and a bioreactor - Meeta Mathur; K. G. Ramawat (Plant Biotechnology Reports, 2008)

Event-based Sediment Yield Modeling using Artificial Neural Network - Raveendra K. Rai; B. S. Mathur (Water Resources Management, 2008)

Transgenic approaches for abiotic stress tolerance in plants: retrospect and prospects - Pooja Bhatnagar-Mathur; V. Vadez; Kiran K. Sharma (Plant Cell Reports, 2008)

Blood Levels of Polycyclic Aromatic Hydrocarbons in Children of Lucknow, India - Vipul K. Singh; Devendra K. Patel; S. Ram; N. Mathur; M. K. J. Siddiqui; Jai Raj Behari (Archives of Environmental Contamination and Toxicology, 2008)

Stress-inducible expression of At DREB1A in transgenic peanut (Arachis hypogaea L.) increases transpiration efficiency under water-limiting conditions - Pooja Bhatnagar-Mathur; M. Jyostna Devi; D. Srinivas Reddy; M. Lavanya; Vincent Vadez; R. Serraj; K. Yamaguchi-Shinozaki; Kiran K. Sharma (Plant Cell Reports, 2007)

Studies on the Genotoxicity of Endosulfan in Different Tissues of Fresh Water Fish Mystus vittatus Using the Comet Assay - Shilpi Sharma; N. S. Nagpure; Ravindra Kumar; Sanjay Pandey; Satish K. Srivastava; Poonam J. Singh; P. K. Mathur (Archives of Environmental Contamination and Toxicology, 2007)

Type-2 diabetes related intermediate phenotypic traits in north Indian diabetics - S. K. Mathur; Piyush Chandra; Sandhya Mishra; Peeyush Ajmera; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2007)

A study of air–sea interaction following the tsunami of 26 December 2004 in the eastern Indian Ocean - V. K. Agarwal; A. Mathur; R. Sharma; N. Agarwal; A. Parekh (International Journal of Remote Sensing, 2007)

Guggulsterone production in cell suspension cultures of the guggul tree, Commiphora wightii, grown in shake-flasks and bioreactors - Meeta Mathur; K. G. Ramawat (Biotechnology Letters, 2007)

Oldest camarasauromorph sauropod (Dinosauria) discovered in the Middle Jurassic (Bajocian) of the Khadir Island, Kachchh, western India - Markus Moser; Umesh B. Mathur; Franz T. Fürsich; Dhirendra K. Pandey; Neera Mathur (PalZ, 2006)

Genetic transformation technology: Status and problems - Kiran K. Sharma; Pooja Bhatnagar-Mathur; Trevor A. Thorpe (In Vitro Cellular & Developmental Biology - Plant, 2005)

Sub-Surface Investigations on Deep Saline Groundwater of Charnockite Rock Formation, Kalpakkam, India - C. Gurumoorthy; P. Sasidhar; V. Arumugham; R. K. Mathur (Environmental Monitoring and Assessment, 2004)

Toxic Effects of Textile Printing Industry Effluents on Liver and Testes of Albino Rats - R. Krishnatrey; S. Sharma; K. P. Sharma; N. Mathur (Bulletin of Environmental Contamination and Toxicology, 2003)

2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) induces oxidative stress in the epididymis and epididymal sperm of adult rats - C. Latchoumycandane; K. C. Chitra; P. P. Mathur (Archives of Toxicology, 2003)

Intercomparison of IRS-P4-MSMR derived geophysical products with DMSP-SSM/I and TRMM-TMI finished products - A. K. Varma; R. M. Gairola; A. K. Mathur; B. S. Gohil; Vijay K. Agarwal (Journal of Earth System Science, 2002)

Rain rate measurements over global oceans from IRS-P4 MSMR - A. K. Varma; R. M. Gairola; Samir Pokhrel; B. S. Gohil; A. K. Mathur; Vijay K. Agarwal (Journal of Earth System Science, 2002)

Effect of nonylphenol on the antioxidant system in epididymal sperm of rats - Chitra K.; Latchoumycandane C.; Mathur P. (Archives of Toxicology, 2002)

Cloning and characterization of an insecticidal crystal protein gene fromBacillus thuringiensis subspecieskenyae - Hari S. Misra; Nivedita P. Khairnar; Manjula Mathur; N. Vijayalakshmi; Ramesh S. Hire; T. K. Dongre; S. K. Mahajan (Journal of Genetics, 2002)

Induction of oxidative stress in rat epididymal sperm after exposure to 2,3,7,8-tetrachlorodibenzo- p -dioxin - Latchoumycandane C.; Chitra K.; Mathur P. (Archives of Toxicology, 2002)

A biologically active constituent of withania somnifera (ashwagandha) with antistress activity - Parvinder Kaur; Sheenu Mathur; Meenakshi Sharma; Manisha Tiwari; K. K. Srivastava; Ramesh Chandra (Indian Journal of Clinical Biochemistry, 2001)

Isolation of two antifungal compounds fromNeolitsea cuipala and their activity against some plant pathogenic fungi - P. Boruah; P. Deka Bhuyan; S. C. Dutta; S. Mohan; R. K. Mathur (Folia Microbiologica, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Database management and analysis for CAPE project using remote sensing and GIS - Ajay Mathur; P K Litoria; P K Sharma; M H Kalubarme (Journal of the Indian Society of Remote Sensing, 1998)

Thymopentin and splenopentin as immunomodulators - Vijay K. Singh; Sumita Biswas; Krishna B. Mathur; Wahajul Haq; Satyendra K. Garg; Shyam S. Agarwal (Immunologic Research, 1998)

Effects of atmospheric boundary layer mixing representations on vertical distribution of passive and reactive tracers - K. Alapaty; R. Mathur (Meteorology and Atmospheric Physics, 1998)

Site suitability evaluation for locating sewage treatment plants using remote sensing and gis — a case study of phillaur and phagwara townships in punjab - P K Litoria; Ajay Mathur; P K Sharma; Charan kamal Singh (Journal of the Indian Society of Remote Sensing, 1997)

Biochemical and morphological changes in some organs of rats in nickel intoxication - A. K. Mathur; Satya V. Chandra; Jairaj Behari; S. K. Tandon (Archives of Toxicology, 1977)

Contribution to the knowledge of the natural enemies ofBissetia steniellus (Hampson) [Lep.: Pyralidae] - K. C. Mathur (BioControl, 1967)